1977
DOI: 10.3171/jns.1977.47.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

Commissural myelotomy

Abstract: The effect of commissural myelotomy in 24 cases with intractable pain is described. The operative technique employed with the operating microscope or magnifying glasses and a special myelotome is outlined. The results suggest an outstanding advantage in patients with bilateral metastases from malignancies except intrapelvic metastases. Patients with lumbar arachnoiditis showed a total failure of pain relief after 2 to 5 years, in spite of good relief temporarily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Internal arcuate fibers then transmit nociceptive input to visceroceptive neurons of the ventral posterolateral thalamus. 2,3,10 New knowledge of this pathway, combined with previous clinical reports of successful pain relief following midline myelotomy, 5,8 led us recently to recommend a modified midline myelotomy to a young woman who was literally dying of lower abdominal pain. In earlier reported successful cases of midline myelotomy in humans, the intent of the operation had been to interrupt the midline commissure over some rostrocaudal length and thereby sever the bilateral crossing fibers of the anterolateral quadrant ascending pain fiber system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Internal arcuate fibers then transmit nociceptive input to visceroceptive neurons of the ventral posterolateral thalamus. 2,3,10 New knowledge of this pathway, combined with previous clinical reports of successful pain relief following midline myelotomy, 5,8 led us recently to recommend a modified midline myelotomy to a young woman who was literally dying of lower abdominal pain. In earlier reported successful cases of midline myelotomy in humans, the intent of the operation had been to interrupt the midline commissure over some rostrocaudal length and thereby sever the bilateral crossing fibers of the anterolateral quadrant ascending pain fiber system.…”
mentioning
confidence: 99%
“…In earlier reported successful cases of midline myelotomy in humans, the intent of the operation had been to interrupt the midline commissure over some rostrocaudal length and thereby sever the bilateral crossing fibers of the anterolateral quadrant ascending pain fiber system. 5,8 A retrospective evaluation of the basis for the pain relief, 10 however, suggests that the benefit was probably derived not from the interruption of the crossing spinothalamic fibers but from the coincidental damage to the midline region of the dorsal columns. Hirshberg and colleagues 10 reached this conclusion in part based on their own autopsy material and on the clinical material of others, which showed that some successful myelotomies had either not been deep enough 4 or had been performed at the wrong rostrocaudal level [11][12][13] to reach the appropriate region of the commissure.…”
mentioning
confidence: 99%
“…These symptoms are reported to generally improve with time and this was seen in our series as well [27,28] . There was also a low incidence (1 patient) of postoperative urinary retention, another complication that has been documented in the literature [24] .…”
Section: Present Seriesmentioning
confidence: 89%
“…Although commissural myelotomy has been used with varying degrees of success in patients with multiple sclerosis or tabes dorsalis, lumbar arachnoiditis remains one indication for which consistently good outcomes have not been seen [5,24] . For patients with strictly localized sacral pain of malignant origin, myelotomy has proven an excellent therapeutic intervention [25] .…”
Section: Evolution Of Myelotomymentioning
confidence: 99%
“…The procedure of commissural myelotomy has recently undergone increased popularity, probably because of the availability of microneurosurgical techniques which allow more accurate bisection of the spinal cord with less risk to the blood vessels [1,7]. Myelotomy is pre ferred over cordotomy in patients with bilateral pain or with pelvic pain.…”
mentioning
confidence: 99%